PENGARUH SISTEM INFORMASI PEMERINTAH DAERAH, TRANSPARANSI, DAN KESIAPAN SDM TERHADAP PELAPORAN KEUANGAN (KOTA PALOPO) - Jihan Sukri; Indah Pratiwi; Mutmainna Mutmainna (Jurnal Riset Terapan Akuntansi, 2026)
This study aims to analyze the effect of the implementation of the Regional Government Information System (SIPD), transparency, and human resource readiness on the quality of financial reporting in the Palopo City Government. Unlike previous research that focused more on information technology in general, this study fills the gap by integrating the specific SIPD, transparency, and human resource readiness in the context of small-city local governments, which are crucial for improving financial accountability in the digital era. A quantitative approach using a survey method was used, with data collected through a Likert-scale questionnaire from 52 employees of the Palopo City Regional Finance and Asset Management Agency (BPKAD) using a total sampling technique. Data analysis was conducted using multiple linear regression. The results indicate that, partially, the implementation of SIPD has no significant effect, while transparency and human resource readiness have a positive and significant effect. Simultaneously, all three variables significantly influence the quality of financial reporting. These findings indicate that improving the quality of regional financial reporting depends not only on information systems but also on strengthening transparency and developing human resource capacity for accountable and effective governance. Keywords: Regional Government Information System (SIPD), transparency, human resource readiness, regional financial reporting.